The Licensors’ Economic Right for Creative Commons Licensed Works Used for Commercial Purposes In Indonesia - Sulistianingsih, Dewi; Safitri, Gianefi (Halu Oleo Law Review, 2019)
A Creative Commons License is a public license which can be used by a creator or an inventor regarding a royalty-free license both for commercial and non-commercial uses. The commercial use of a creation financially inflicts the licensor since there is no economic right from the royalty from the user of the creation. This paper is a result of a study which applied a normative juridical approach. The study aims to find out the protection of economic right of the licensor for his or her creation, which is under creative commons license, which is used for commercial purposes. The economic right protection of the licensor whose work is under common creative license which is used commercially is the same as that of other licenses because a creative commons license is basically the same as other license agreements which bind parties involved in an agreement. The protection is given through the Act of the Republic of Indonesia Number 28 Year 2003 Concerning Copyright.